2020
DOI: 10.11604/pamj.supp.2020.35.2.24692
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of D-dimer in patients with COVID-19: prognosis value

Abstract: Introduction: coronavirus disease is now a global pandemic due to rapid human-to-human transmission. It can cause mild to fatal respiratory, cardiovascular, and neurological diseases. We aimed to find out whether elevated D-dimer levels are a predictor of the bad progression of COVID-19 to help reducing the mortality. Methods: the data of COVID-19 patients from March 21, 2020 to April 24, 2020 were retrieved from the Cheick Khalifa Hospital database. We used the receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
(15 reference statements)
1
8
0
3
Order By: Relevance
“…This finding is in accordance with most of the published research on the topic. Zhang et al found an AUC of 0.89 in their study, whereas Oualim et al reported an AUC of 0.775 and Peiro et al reported an AUC of 0.756 [ 8 , 17 , 18 ]. Our AUC value is higher than some reported values of AUC, including Naymagon et al who showed an AUC of 0.694, Soni et al, who showed an AUC of 0.683, and He et al who reported an AUC of 0.661 [ 9 , 12 , 19 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding is in accordance with most of the published research on the topic. Zhang et al found an AUC of 0.89 in their study, whereas Oualim et al reported an AUC of 0.775 and Peiro et al reported an AUC of 0.756 [ 8 , 17 , 18 ]. Our AUC value is higher than some reported values of AUC, including Naymagon et al who showed an AUC of 0.694, Soni et al, who showed an AUC of 0.683, and He et al who reported an AUC of 0.661 [ 9 , 12 , 19 ].…”
Section: Discussionmentioning
confidence: 91%
“…The optimal cutoff value for admission D-dimer for predicting mortality has not been agreed upon in the current literature. Some studies have identified optimal cutoffs based on ROC curves, but the values range anywhere from 0.67 to 2.025 μg/ml, with large variation in sensitivity and specificity as well [ 8 , 9 , 12 , 17 19 ]. A French multicenter study published in May 2021 identified the cutoff value for admission D-dimer as 1.113 μg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…While a D-dimer elevation of 3 times or more at the first admission was considered risky for embolism, a 4-fold or higher D-dimer level during follow-up was found to be a good indicator for mortality in hospitalized patients (17). Similarly, if D-dimer elevation still persists after the 5 th day, this may be an indicator for severe COVID-19 disease and mortality (18). In another study, higher mortality rates were found in patients with D-dimer levels above 2000 ng/ml compared to patients with D-dimer levels below 2000 ng/ml (19).…”
Section: Discussionmentioning
confidence: 96%
“…5 Kadar D-dimer pada hari kelima perawatan >1.360ng/ ml berhubungan dengan perburukan kondisi dan peningkatan mortalitas penderita COVID-19. 14 Pada penelitian ini sebanyak 26,19% penderita meninggal pada kelompok COVID-19 berat secara bermakna lebih tinggi dibandingkan pada COVID-19 tidak berat (81,81% berbanding 18,18% dengan p = 0,001). Kadar D-dimer yang tinggi juga diperkirakan dapat memprediksi keparahan COVID-19, komplikasi paru-paru, dan kejadian tromboemboli.…”
Section: Diskusiunclassified